Free-Flow Speed For Four-Lane Highways With Level Terrain In Rural And Suburban Areas In Peninsular Malaysia - Azai, Tuti Azmalia (2013)
Free-flow speed plays an important role in determining the highway performance of four-lane highways. The main objective of this study is to determine the appropriate models of free-flow speed on uninterrupted four-lane highways based on local traffic conditions in Malaysia. To carry out this study, data was collected at 16 sites (64 lanes) around Peninsular Malaysia. CCTV was used to collect field data and the collected data was reduced using TRAISTM Advanced SRM 3.2 software. Statistical analysis by SPSS 20 software was used to analyze the data of free-flow speed. Freeflow speed in each lane was measured using three methods which are based on linear speed-density relationship (Greenshield, 1935) which is Method 1, average speed of vehicles during low flow rate (U.S. HCM, 2000) which is Method 2 and average speed with headway ≥ 8 s which is Method 3. The results showed that the mean freeflow speed between Method 1, 2 and 3 was found to be not significantly different. Subsequently, multiple linear regression techniques was used to derive predictive free-flow speed models. The developed regression model showed good correlation with high value of coefficient of determination, R2. In addition, performance indicator (PI) showed that the model which is based on free-flow speed of cars with headway ≥ 8 s was selected as the most suitable model to be used in Malaysia roadway condition. Finally, sensitivity analysis showed that free-flow speed tended to be lower during worst geometrical conditions and lane width was the most sensitive parameter compared with other parameters.